Hubungan ESBL dengan Lama Rawat Inap pada Pasien Ulkus Kaki Diabetes - Melynda Dyah Pratiwi; Yuniati Yuniati; Yuliana Rahmah Retnaningrum (Jurnal Medika : Karya Ilmiah Kesehatan, 2022)
Diabetic Foot Ulcer (DFU) is a condition of foot ulcers caused by neuropathy disorders. The prevalence of DFU in Indonesia is around 15% with an amputation rate of 30% and a mortality rate of 32%. DFU is known as a chronic wound with a long healing time. Infection with Extended-Spectrum Beta-Lactamase (ESBL) is an important predictor in determining the optimal antibiotic regimen. The study aim was to determine the association between ESBL infection with length of stay in DFU patients at Abdoel Wahab Sjahranie Hospital, Samarinda. This study used analytical observational method with a cross-sectional study approach. The research data were gathered from the medical records of DFU patients at Abdoel Wahab Sjahranie Hospital Samarinda from the period of 2020–2022 with a purposive sampling method. There were 108 patients selected as samples through inclusion and exclusion criteria. The statistical bivariate analysis was performed using Chi-Square test. The results showed that there was no association between ESBL (p=0.676) towards length of stay in DFU patients at Abdoel Wahab Sjahranie Hospital Samarinda.